Peculiarities of Data Protection as a Separate Legal Institution - Prystai, Rostyslav (Teisė, 2025)
The institute of personal data protection currently functions as a relatively separate group of legal norms aimed at protecting rights related to the processing of personal data. The immediate object of its protection is personal data, hence the right to protection of personal data and the right to private life of a person which are in a close relationship. This relationship is expressed in the practice of national courts, ECHR, CJEU, etc., which interpret these rights differently (as lex specialis or equivalent rights). The Institute for the protection of personal data under GDPR also has its own characteristics and reflects the vision of the European legislator regarding their correlation and protection. However, the lack of scientific emphasis and the difficulty in defining the boundary and relationship between data protection and privacy still has an impact on law enforcement and creates a need for research of the institution of personal data protection. The article examines the peculiarities of data protection as a separate legal institution and its relationship with the privacy protection. The obtained results can be used for further scientific research and practical application.
Keywords: personal data protection; right to privacy; legal institution; General Data Protection Regulation